Boldness is related to the development of the cephalic crest in the male of the river blenny Salaria fluviatilis (Asso, 1801). Issue 3 (1st June 2014) - Fabre, Noëlle; GarcÍa-Galea, Eduardo; Vinyoles, Dolors
Abstract: Boldness is defined as the tendency of an individual to take risks when exposed to novel objects or situations. The main aim of this work was to dilucidate if boldness was related to the development of the secondary sexual traits (SSTs) in the male of the river blenny Salaria fluviatilis, a freshwater fish which takes care of eggs. As a second objective SSTs effect on parental status adoption was also be explored. Wild young fish were caught in the Segre River (Ebro basin) in November 2010. Fish were kept in five aquaria in groups of eight males and eight females with artificial nests. Boldness (boldness score and hesitancy) of males (initially with little SSTs development) was tested as the time required to exit a refuge when exposed to a new environment. Fish were mantained in the same aquaria for several months, and males' SSTs development and reproductive behaviour were monitored. Boldness score was negatively associated to cephalic crest development. Hesitancy was negatively related to male length and was also influenced by the interaction between male length and cephalic crest. Parental status acquisition was positively related to the male's length, marginally related to anal gland development, and non-related to cephalic crest. These results suggest an intrasexual role of the crest as an informative trait of boldness (honest signal) which might not necessarily be chosen by the females. It is also discussed that correlational selection could be responsible for linking boldness and growth rate in this species. Sexual selection, in addition to having directed the evolution of secondary sexual traits, might have favored certain personality traits (e.g. boldness) associated with the achievement of a larger body length.